Factors Influencing Ecopreneurship Development in the Plastic Waste Handicraft Sector in Surabaya City - Wininatin Khamimah; Tegowati, Tegowati (FEB - Universitas Lampung, 2025)
Waste is one of the major problems for society because its impact is very severe if not handled properly. But not many residents can see the enormous economic potential of waste, which could yield multiple profits if it is creatively processed into various recycled products, commonly called ecocrafts. Ecopreneurship embodies the capacity to identify everyday community challenges and transform them into viable business opportunities that simultaneously address environmental issues. This study aims to examine how environmental, personal, and social factors affect the development of ecopreneurship in Surabaya's plastic waste handicraft sector. Using a quantitative approach with a sample of 30 ecopreneurs and SPSS-based analysis, results show that environmental and personal factors significantly influence ecopreneurship, while social factors do not. These findings suggest that individual motivation and external environmental conditions play a more critical role than community support. The study provides useful insights for local policy makers to strengthen support for sustainable entrepreneurship.